2016
DOI: 10.1002/jsfa.8069
|View full text |Cite
|
Sign up to set email alerts
|

Effect of two doses of urea foliar application on leaves and grape nitrogen composition during two vintages

Abstract: Urea foliar applications can be an interesting tool for decreasing grapevine nitrogen deficiencies. This method of nitrogen implementation in the vineyard could avoid sluggish fermentation problems during winemaking, enhance must nitrogen composition, and contribute to improving wine quality. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
48
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 36 publications
10
48
1
Order By: Relevance
“…These concentrations are similar to the anthocyanin concentrations in the same cultivar of Tempranillo from A.O.C. Rioja (1500-1910 mg kg −1 ), 70 Cabernet Sauvignon (1247.7 mg kg −1 ), 6 and Cabernet Sauvignon (1577 mg kg −1 ) or Sangiovese (1541 mg kg −1 ), 71 but higher than the concentrations in Mencía grapes from Ribeira Sacra (439-573 mg kg −1 ) 72 and Nebbiolo (550 mg kg −1 ). 73 In their study with Tempranillo grapes from different types of soil, Ramos and Martínez de Toda 30 observed that within a given year, lower anthocyanins values were recorded for the vines cultivated in soils with the lowest organic carbon content, the lowest percentage of coarse elements, and the highest water availability in the soil, whereas the highest anthocyanin values were always in vines from the soils with a higher content of sand and coarse elements and with the least water available in the soil.…”
Section: Anthocyanin Content Of Grapessupporting
confidence: 82%
“…These concentrations are similar to the anthocyanin concentrations in the same cultivar of Tempranillo from A.O.C. Rioja (1500-1910 mg kg −1 ), 70 Cabernet Sauvignon (1247.7 mg kg −1 ), 6 and Cabernet Sauvignon (1577 mg kg −1 ) or Sangiovese (1541 mg kg −1 ), 71 but higher than the concentrations in Mencía grapes from Ribeira Sacra (439-573 mg kg −1 ) 72 and Nebbiolo (550 mg kg −1 ). 73 In their study with Tempranillo grapes from different types of soil, Ramos and Martínez de Toda 30 observed that within a given year, lower anthocyanins values were recorded for the vines cultivated in soils with the lowest organic carbon content, the lowest percentage of coarse elements, and the highest water availability in the soil, whereas the highest anthocyanin values were always in vines from the soils with a higher content of sand and coarse elements and with the least water available in the soil.…”
Section: Anthocyanin Content Of Grapessupporting
confidence: 82%
“…reported an increase in YAN in musts after Ur foliar application to Tempranillo and Cabernet Sauvignon varieties with respect to untreated grapevines. Pérez‐Álvarez et al . reported that the Ur foliar treatment of Tempranillo grapevines did not affect the must YAN content compared with control samples.…”
Section: Resultsmentioning
confidence: 99%
“…Garde-Cerdán et al 8 and Gutiérrez-Gamboa et al 11 reported an increase in YAN in musts after Ur foliar application to Tempranillo and Cabernet Sauvignon varieties with respect to untreated grapevines. Pérez-Álvarez et al 12 reported that the Ur foliar treatment of Tempranillo grapevines did not affect the must YAN content compared with control samples. As previously mentioned by different authors, the effect of foliar applications of elicitors and nitrogen sources showed slight differences between treatments.…”
Section: Enological Parameters and Yanmentioning
confidence: 99%
“…However, in terms of vintage and variety, urea applied to Monastrell and Tempranillo grapevines had little effect on grape amino acid concentrations . Also, it has been reported that the effects of year on the increase in must total amino acid concentrations through urea foliar applications are more important than the doses applied …”
Section: Biostimulants To Improve Grape and Wine Qualitymentioning
confidence: 99%
“…However, with this type of application, there is the risk of nitrogen leaching and denitrification, so the use of organic additions can help to avoid these environmental problems for the soil . Therefore, foliar application has been a recent technique that has provided improvements to must quality in relation to the amino acid and phenolic and volatile compound concentrations . Nevertheless, some studies have reported that the use of foliar applications can have little, or indeed negative, effects on grape berry quality …”
Section: Introductionmentioning
confidence: 99%